Specialized strut-and-tie method for rapid strength prediction of bridge pier caps. (1st November 2019) - Baniya, Pappu; Guner, Serhan
Highlights: An innovative strut-and-tie methodology (STM) to predict the capacities of deep pier caps. A graphical solution algorithm and associated computer code (STM-CAP). Similar modeling time as the sectional method but significantly more accurate. Predicts up to three times higher shear load capacities than the sectional method. Abstract: Deep pier caps possess additional shear strength due to the formation of the strut action which cannot be captured by the traditional sectional method. The strut-and-tie method (STM) is a suitable method for capturing the deep beam action. The application of the STM, however, has many challenges including creating and optimizing a valid truss model, performing an indeterminate truss analysis, calculation of nodal and elemental stress limits, etc. The objective of this study is to explore innovative strategies to reduce the complexity of the STM by developing a strut-and-tie methodology to rapidly and accurately predict the shear capacities of deep pier caps. A graphical solution algorithm and associated computer code is developed to generate and analyze efficient strut-and-tie models while intuitively educating engineers in the correct use of the methodology. The accuracy of the methodology is assessed by modeling eight existing bridge pier caps with a general-purpose strut-and-tie method. In addition, nonlinear finite element analyses of the same pier caps are performed for an in-depth investigation and comparisons of the governing behaviors, strengths, and modes of failure with those obtained from the proposed methodology. Although not valid for deep beams, the sectional method calculations are performed to demonstrate the consequences of using it. The relationship between the shear span-to-depth ratio and the shear strength predictions from all three methods are compared for twenty-one regions. The proposed methodology has general applicability for modeling deep pier caps and is shown to provide similar modeling time and effort to the sectional method with accuracies comparable to those obtained from the nonlinear finite element analysis.